Mapeamento eletroanatômico epicárdico e endocárdico combinado associado à ablação por radiofrequência em pacientes com cardiomiopatia chagásica e taquicardia ventricular - Henz, Benhur Davi [UNIFESP] (2009)
Background: Slow conduction scarred areas are related with ventricular tachycardia (VT) arrhythmogenesis in nonischemic cardiomyophathy. The purpose of this study was to characterize the substrate in both epicardial and endocardial surfaces of the left ventricle and to evaluate the effectiveness of substrate mapping and ablation for VT in Chagas cardiomyopathy. Methods and Results: Seventeen patients were evaluated prospectively using a simultaneous epicardial and endocardial electroanatomical substrate mapping and ablation. With a mean of 201±94 epicardial and 169±77 endocardial points, the epicardial voltage areas ≤0.5mV were 56.8 ± 40.6 (range 4.4 to 154.8 cm2) as compared to 22.5 ± 15.8cm2 (range 5.4 to 61 cm2) (p=0.004) in the endocardium. Analyzing the epicardial surface, there was a strong correlation between the bipolar voltage electrograms and the electrogram duration at the epicardium during sinus rhythm (r= 0.897, p<0.0001). Acute success was obtained in 83.3% of procedures with no serious complications. At the end of follow-up from 14 patients with acute success, 11 (78.6%) had been event-free based on ICD interrogation logs. Conclusion: Chronic Chagas cardiomyophathy patients have larger epicardial as compared to endocardial substrate areas. Combined epicardial endocardial substrate mapping and ablation during sinus rhythm proves effective in preventing VT recurrences and appropriate ICD therapies.